Fungsionalisasi UU No. 23 Tahun 2004 dalam Penanggulangan Tindak Pidana dalam Lingkup Rumah Tangga (Analisis Putusan No. 98/Pid.B/2007/PN.YK dan Putusan No. 273/Pid.B/2010/PN.SLMN.) - Anny Retnowati (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research was conducted to answer two problems: first, the counter measures for criminal acts in households, especially the acts related to two decrees, those are Decree No. 98/Pid.B/2007/PN.YK and Decree No. 273/Pid.B/2010/PN.SLMN. Second, the settlement taken related to those two decrees. The research used normative method. The findings show that: first, criminal acts in household scope especially ones related to Decree No. 98/Pid.B/2007/PN.YK and Decree No. 273/Pid.B/2010/PN.SLMN are countered by functionalize Article 41 verse (1) of Law No. 23 of 2004 on Domestic Violence Regulation. Second, the settlement of those two cases is conducted using repressive legal process that can prove that those two defendants had convincingly and legally conducted criminal act in form of violence against their wives. Consequently, District Court of Yogyakarta decided six-month imprisonment, and District Court of Sleman decided one-year imprisonment for the defendants.